2015
DOI: 10.1007/s12035-015-9271-6
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association Between Serum Uric Acid Levels and Alzheimer’s Disease Risk

Abstract: The association between Alzheimer's disease and uric acid levels had gained great interest in recent years, but there was still lack of definite evidence. A systematic review and meta-analysis of relevant studies was performed to comprehensively estimate the association. Relevant studies published before October 26, 2014, were searched in PubMed, Embase, and China Biology Medicine (CBM) databases. Study-specific data were combined using random-effects or fixed-effects models of meta-analysis according to betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 42 publications
(85 reference statements)
3
45
0
2
Order By: Relevance
“…65 84 Discordance in the statistical significance was present for two outcomes: diabetic neuropathy (n=2) 51 53 and Alzheimer's disease (n=4). 57 58 73 80 After removing the overlapping meta-analyses (which were conducted in the same population for the same outcome), 76 unique meta-analyses were retained. The meta-analyses reported a wide range of outcomes (table 1): cardiovascular outcomes (n=13), diabetes related outcomes (n=9), kidney disorders (n=7), neurocognitive disorders (n=11), cancer outcomes (n=6), all cause or cause specific mortality (n=22), and other outcomes (n=8).…”
Section: Meta-analyses Of Observational Studiesmentioning
confidence: 99%
“…65 84 Discordance in the statistical significance was present for two outcomes: diabetic neuropathy (n=2) 51 53 and Alzheimer's disease (n=4). 57 58 73 80 After removing the overlapping meta-analyses (which were conducted in the same population for the same outcome), 76 unique meta-analyses were retained. The meta-analyses reported a wide range of outcomes (table 1): cardiovascular outcomes (n=13), diabetes related outcomes (n=9), kidney disorders (n=7), neurocognitive disorders (n=11), cancer outcomes (n=6), all cause or cause specific mortality (n=22), and other outcomes (n=8).…”
Section: Meta-analyses Of Observational Studiesmentioning
confidence: 99%
“…Previous epidemiological studies proved that decreased uric acid levels were associated with an increased risk of PD and AD 23 , 24 . UA has the ability to reduce oxidative stress, to inhibit glutamate toxicity, and to protect central nervous system 8 , 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Increasing numbers of studies have found that uric acid plays an important role in cognitive impairment. 6 10 A relationship between uric acid and cognitive function has been demonstrated, and studies have investigated the association between uric acid and cognitive dysfunction in the context-specific diseases and various types of dementia. However, the relationship between uric acid and MCI has seldom been studied.…”
Section: Introductionmentioning
confidence: 99%